The Relationship between Energy Transition, Industrialization and Employment: A GMM Panel Var Approach - Poumie, BOKER; Guivis, NKEMGHA ZEUFACK (Energy Economics Letters, 2021)
Using quarterly data for the period 2013Q1-2017Q1, this study explores the relationship between energy transition, industrialization, and employment in the panel of developed and emerging countries. The GMM panel VAR proposed by Abrigo and Love (2016) and Granger causality test are used. After confirming the presence of unit root in our variables, the results of GMM panel VAR reveal that industrialization and employment negatively affect energy transition while energy transition does not have any effect on industrialization and employment. Furthermore, the Granger causality indicates a unidirectional relationship going from industrialization and employment to energy transition. Our findings also support major differences in the relationship between the studied variables depending on the country being emerging or advanced. These results may have policy implications for the more energy-efficient system of countries.